A comparative typological analysis of the Jewish apocalyptic features and Zimbabwean apocalyptic music: a reflection on Hosiah Chipanga’s music - Samhika, Bishow (Scriptura, 2020)
Zimbabwean apocalyptic literature (songs of liberation) was produced during the colonial and post-colonial era to critique oppressive measures. Apocalyptic literature evinces itself in the following characteristics: symbolism, dualism, pseudonymity, eschatology, revelation, vaticinium ex eventu and exhortations. Zimbabwean apocalyptic music, like Jewish apocalyptic literature was developed to answer the difficulties associated with the justice of God in the light of suffering under repressive leadership. In the Jewish context, the genre developed during the post-exilic period. In the context of this article, songs of liberation in Zimbabwe form this type of apocalyptic literature. One would assume that there was a direct influence of Jewish apocalypticism on Zimbabwean apocalyptic music. However, it is undeniable that Jewish apocalyptic ideology or features are very prominent in Zimbabwean liberation music. Although apocalyptic music in Zimbabwe is attributed to musicians like Thomas Mapfumo, Oliver Mtukudzi, Leonard Zhakata, Zex Manatsa and Paul Madzore, this article focuses on Chipanga's apocalyptic music, which exhibits features similar to those found in biblical apocalypticism.